Electrode, all-solid-state battery, and method for manufacturing all-solid-state battery
Patent Information
- Application Number
- JP2022010724
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-01-27
Smart Images

Figure 0007640479000003 
Figure 0007640479000004 
Figure 0007640479000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode, an all-solid-state battery, and a method for manufacturing an all-solid-state battery. [Background technology]
[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode and a negative electrode, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent.
[0003] For example, Patent Document 1 discloses an all-solid-state battery including a first current collector foil, a first composite layer, a solid electrolyte layer, a second composite layer, and a second current collector foil, and a carbon material layer having an adhesive function is provided on the surface of the second current collector foil facing the second composite layer. Patent Document 2 discloses an all-solid-state battery including a stacked battery unit including a first current collector layer, a first active material layer, a solid electrolyte layer, a second active material layer, a second current collector layer, a second active material layer, a solid electrolyte layer, a first active material layer, and a first current collector layer stacked in this order, and the first current collector layer and the first active material layer stacked adjacent to each other are bonded to each other with an adhesive.
[0004] Patent Document 3 discloses an all-solid-state battery having two or more battery units in which a current collector of a first electrode, an active material layer of the first electrode, a solid electrolyte layer, an active material layer of a second electrode, a current collector of a second electrode, an active material layer of the second electrode, a solid electrolyte layer, and an active material layer of the first electrode are stacked in this order, and has an adhesive means for adhering the current collector of the first electrode of the battery unit to the battery unit stacked adjacent to the current collector. In addition, Patent Document 4 discloses an anisotropic conductive material in which specific conductive particles are dispersed in a binder resin, although it is in a different field from batteries. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-129485 A [Patent Document 2] JP 2020-140932 A [Patent Document 3] JP 2017-204377 A [Patent Document 4] JP 2019-021635 A Summary of the Invention [Problem to be solved by the invention]
[0006] It is known to provide an adhesive carbon material layer between a current collector and an active material layer, as in Patent Document 1. On the other hand, when the temperature of an all-solid-state battery becomes high (e.g., 80° C.), the adhesiveness of the carbon material layer decreases, and the adhesion between the current collector and the active material layer may decrease.
[0007] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an electrode having good adhesion between a current collector and an active material layer even at high temperatures. [Means for solving the problem]
[0008] The present disclosure provides an electrode for use in an all-solid-state battery, the electrode having a current collector, an adhesive carbon material layer, and an active material layer in this order in a thickness direction, the carbon material layer containing a carbon material, a dispersant, and a binder.
[0009] According to the present disclosure, by disposing a specific carbon material layer between a current collector and an active material layer, an electrode having good adhesion between the current collector and the active material layer even at high temperatures can be obtained.
[0010] In the above disclosure, the proportion of the dispersed material in the carbon material layer may be 1% by weight or more.
[0011] In the above disclosure, the proportion of the dispersed material in the carbon material layer may be 35% by weight or less.
[0012] In the above disclosure, in the carbon material layer, a weight ratio of the dispersion material to the carbon material may be 0.05 or more and 1.2 or less.
[0013] In the above disclosure, the carbon material layer may contain the binder as a main component.
[0014] In the above disclosure, the proportion of the binder in the carbon material layer may be 50% by weight or more.
[0015] In the above disclosure, in the carbon material layer, a weight ratio of the binder to the carbon material may be 2.0 or more.
[0016] In the above disclosure, in the carbon material layer, a weight ratio of the binder to the carbon material may be 2.8 or more.
[0017] In the above disclosure, the dispersing material may include at least one of a vinyl resin and a cellulose derivative.
[0018] In the above disclosure, the dispersing material may include polyvinyl alcohol.
[0019] In the above disclosure, the binder may include at least one of an acrylic binder and a methacrylic binder.
[0020] In the above disclosure, the oil absorption of the carbon material is 175 cm 3 / 100g or more.
[0021] In the above disclosure, the carbon material may include carbon black.
[0022] In the above disclosure, the binder may be present at least on the surface of the carbon material layer facing the current collector.
[0023] In the above disclosure, the peel strength between the current collector and the active material layer may be 0.10 N / cm or more at 80°C.
[0024] The present disclosure also provides an all-solid-state battery including a first electrode, a second electrode, and a solid electrolyte layer disposed between the first electrode and the second electrode, wherein at least one of the first electrode and the second electrode is the electrode described above.
[0025] According to the present disclosure, at least one of the first electrode and the second electrode is the above-mentioned electrode, and therefore, an all-solid-state battery having good durability at high temperatures is obtained.
[0026] In the above disclosure, the all-solid-state battery may include a first electrode A and a first electrode B as the first electrode, and a solid electrolyte layer A and a solid electrolyte layer B as the solid electrolyte layer, the second electrode may include a second current collector, a second active material layer A formed on one surface of the second current collector, and a second active material layer B formed on the other surface of the second current collector, and the all-solid-state battery may include the first electrode A, the solid electrolyte layer A, the second electrode, the solid electrolyte layer B, and the first electrode B in this order in a thickness direction, and at least one of the first electrode A and the first electrode B may be the electrode.
[0027] The present disclosure also provides a method for producing an all-solid-state battery, comprising: a preparation step of preparing a precursor laminate having a first active material layer A, a solid electrolyte layer A, a second active material layer A, a second current collector, a second active material layer B, a solid electrolyte layer B, and a first active material layer B in this order in a thickness direction; and a first arrangement step of arranging a first current collector A on the first active material layer A in the precursor laminate via a first carbon material layer containing a carbon material, a dispersant, and a binder.
[0028] According to the present disclosure, by disposing the first current collector A on the first active material layer A with the first carbon material layer interposed therebetween, an all-solid-state battery with good durability at high temperatures can be obtained.
[0029] In the above disclosure, the method may include a second disposing step of disposing a first current collector B on the first active material layer B in the precursor laminate via a second carbon material layer containing a carbon material, a dispersion material, and a binder. Effect of the Invention
[0030] The present disclosure has an effect of providing an electrode having good adhesion between a current collector and an active material layer even at high temperatures. [Brief description of the drawings]
[0031] [Figure 1] 1 is a schematic cross-sectional view illustrating an electrode according to the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 3] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Figure 4] 1A to 1C are schematic cross-sectional views illustrating a method for producing an all-solid-state battery according to the present disclosure. [Diagram 5] FIG. 1 is a schematic plan view illustrating an all-solid-state battery according to the present disclosure. [Figure 6] 1 shows the results of peel strength measurement for the all-solid-state batteries obtained in Examples 1 to 7 and Comparative Examples 1 and 2. [Figure 7] 1 shows the results of resistance measurement for the all-solid-state batteries obtained in Examples 1 to 7 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, the electrodes, all-solid-state batteries, and manufacturing methods of all-solid-state batteries in the present disclosure will be described in detail with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, in this specification, when expressing an aspect in which another member is arranged on a certain member, the term "above" includes both a case in which another member is arranged directly above a certain member so as to be in contact with the certain member, and a case in which another member is arranged above a certain member via another member, unless otherwise specified.
[0033] A. Electrode 1 is a schematic cross-sectional view illustrating an electrode in the present disclosure, specifically, a schematic cross-sectional view illustrating a positive electrode in the present disclosure. The positive electrode 10 shown in FIG. 1 is a cross-sectional view of a positive electrode current collector 1, a carbon material layer 3 having adhesiveness, and a positive electrode active material layer 2, which are arranged in a thickness direction D. T 1, the positive electrode current collector 1 and the carbon material layer 3 are in contact with each other. Similarly, the carbon material layer 3 and the positive electrode active material layer 2 are in contact with each other. The carbon material layer 2 contains a carbon material, a dispersant, and a binder.
[0034] According to the present disclosure, by disposing a specific carbon material layer between the current collector and the active material layer, an electrode having good adhesion between the current collector and the active material layer at high temperatures is obtained. As described above, when the all-solid-state battery reaches a high temperature (e.g., 80°C), the adhesion of the carbon material layer decreases, and the adhesion between the current collector and the active material layer may decrease. For example, since the all-solid-state battery generates heat due to the power generation reaction, the temperature of the all-solid-state battery may reach a high temperature depending on the operating conditions of the all-solid-state battery. In addition, it is presumed that the reason for the decrease in adhesion between the current collector and the active material layer is that the binder softens at high temperatures.
[0035] In the present disclosure, a dispersing agent that improves the dispersibility of the carbon material is added to the carbon material layer. This allows the carbon material to be highly dispersed in the carbon material layer. As a result, even if the binder softens at high temperatures, the highly dispersed carbon material maintains a high viscosity, and it is estimated that the decrease in adhesion between the current collector and the active material layer is also suppressed. In addition, by improving the dispersibility of the carbon material, even if the ratio of the binder in the carbon material layer is increased, a good ion conduction path is maintained. As a result, an increase in resistance is suppressed. That is, when the ratio of the binder in the carbon material layer is increased, it is possible to improve the adhesion between the current collector and the active material layer and suppress the increase in resistance. In addition, when the ratio of the binder in the carbon material layer is increased, there is also the advantage that the decrease in adhesion between the current collector and the active material layer can be further suppressed.
[0036] 1. Carbon material layer The carbon material layer in the present disclosure is disposed between the current collector and the active material layer. The carbon material layer has an adhesiveness sufficient to improve the adhesion between the current collector and the active material layer. The carbon material layer contains a carbon material, a dispersing material, and a binder. On the other hand, the carbon material layer preferably does not contain an active material. Similarly, the carbon material layer preferably does not contain a solid electrolyte.
[0037] (1) Dispersion material The dispersing material in the carbon material layer improves the dispersibility of the carbon material in the carbon material layer. The dispersing material is, for example, a water-soluble material. The water-soluble material refers to a material that completely dissolves in water without separation or precipitation when 1 g of a target material is added to 99 g of water at 25° C., stirred, and left at 25° C. for 24 hours. The water-soluble material is preferably a water-soluble resin. Examples of the dispersing material include vinyl resins and cellulose derivatives. Examples of the vinyl resin include polyvinyl alcohol, polyvinylpyrrolidone, and polyvinyl butyral. Examples of the cellulose derivative include carboxymethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose. The carbon material layer may contain only one type of dispersing material, or may contain two or more types of dispersing materials.
[0038] The proportion of the dispersion material in the carbon material layer is, for example, 1% by weight or more, and may be 5% by weight or more. If the proportion of the dispersion material is too small, the dispersion effect of the dispersion material may not be sufficiently obtained. On the other hand, the proportion of the dispersion material in the carbon material layer is, for example, 50% by weight or less, and may be 35% by weight or less. If the proportion of the dispersion material is too high, the proportions of the carbon material and the binder become relatively low, which may result in high resistance or low adhesion.
[0039] In the carbon material layer, the weight ratio of the dispersion material to the carbon material is, for example, 0.01 or more, may be 0.05 or more, or may be 0.1 or more. If the weight ratio of the dispersion material is too small, the dispersion effect of the dispersion material for the carbon material may not be sufficiently obtained. On the other hand, the weight ratio of the dispersion material in the carbon material layer is, for example, 1.5 or less, may be 1.2 or less, or may be 1.0 or less. If the weight ratio of the dispersion material is too high, the ratio of the carbon material and the binder becomes relatively low, and the resistance may increase or the adhesion may decrease.
[0040] (2) Carbon materials The carbon material in the carbon material layer imparts electronic conductivity to the carbon material layer. Examples of the carbon material include carbon black, carbon fiber, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the carbon black include acetylene black (AB), furnace black (FB), and ketjen black (KB). The carbon material may be a particulate carbon material or a fibrous carbon material. The average particle size (D 50 ) is, for example, 10 nm or more and 50 μm or less, and may be 100 nm or more and 20 μm or less.
[0041] The oil absorption of the carbon material is not particularly limited, but is, for example, 68 cm 3 / 100g or more, 175cm 3 The oil absorption of a carbon material is an index showing the degree of development of the structure in which the particles of the carbon material are fused together, and generally, the greater the oil absorption of the carbon material, the more developed the structure is. Even if the binder softens at high temperatures, the developed structure of the carbon material can provide strength to the carbon material layer and suppress a decrease in the adhesion between the current collector and the active material layer. The oil absorption of a carbon material can be determined by having the carbon material absorb DBP (dibutyl phthalate) using an absorption meter.
[0042] The proportion of the carbon material in the carbon material layer is, for example, 10% by weight or more, and may be 15% by weight or more. If the proportion of the carbon material is too small, the electron conduction path may not be sufficiently formed, and the resistance may be high. On the other hand, the proportion of the carbon material in the carbon material layer is, for example, 50% by weight or less, and may be 35% by weight or less. If the proportion of the carbon material is too high, the proportions of the dispersant and binder become relatively low, and the dispersion effect of the carbon material may be reduced, or the adhesiveness may be reduced.
[0043] (3) Binder The binder in the carbon material layer imparts adhesiveness to the carbon material layer. Examples of the binder include acrylic binders such as polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, polyhexyl acrylate, poly2-ethylhexyl acrylate, polydecyl acrylate, and polyacrylic acid; methacrylic binders such as polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, poly2-ethylhexyl methacrylate, and polymethacrylic acid; fluoride binders such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, and fluorine rubber; and rubber binders such as butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber.
[0044] The binder preferably contains at least one of an acrylic binder and a methacrylic binder. This is because the acrylic binder and the methacrylic binder have a large change in elastic modulus with temperature, and therefore the workability is high when bonding the current collector and the active material layer via the carbon material layer. The binder may be a water-soluble material.
[0045] The glass transition temperature (Tg) of the binder is not particularly limited, but may be, for example, 30° C. or lower, or 25° C. or lower. On the other hand, the glass transition temperature (Tg) of the binder is, for example, −35° C. or higher. The glass transition temperature (Tg) of the binder can be determined based on JIS K7121 and JIS K7122.
[0046] The proportion of the binder in the carbon material layer is, for example, 20% by weight or more, may be 30% by weight or more, or may be 50% by weight or more. If the proportion of the binder is too small, the adhesion between the current collector and the active material layer may be reduced. On the other hand, the proportion of the binder in the carbon material layer is, for example, 90% by weight or less, may be 80% by weight or less. If the proportion of the binder is too high, the proportions of the carbon material and the dispersing material become relatively low, which may increase the resistance or reduce the dispersion effect of the carbon material.
[0047] The carbon material layer may contain a binder as a main component. The "main component" refers to the component with the highest weight ratio in the carbon material layer. For example, when the carbon material layer has a binder ratio of 40% by weight, a carbon material ratio of 30% by weight, and a dispersion material ratio of 30% by weight, the carbon material layer is determined to contain a binder as a main component. On the other hand, the carbon material layer may not contain a binder as a main component. In that case, the carbon material layer preferably contains at least one of a carbon material and a dispersion material as a main component.
[0048] In the carbon material layer, the weight ratio of the binder to the carbon material is, for example, 0.8 or more, may be 1.5 or more, may be 2.0 or more, may be 2.4 or more, or may be 2.8 or more. If the weight ratio of the binder is too low, the adhesion between the current collector and the active material layer may be reduced. On the other hand, the weight ratio of the binder in the carbon material layer may be, for example, 7.0 or less, may be 5.0 or less. If the weight ratio of the binder is too high, the ratio of the carbon material and the dispersing material may be relatively low, which may increase the resistance or reduce the dispersion effect of the carbon material.
[0049] (4) Carbon material layer The carbon material layer in the present disclosure contains a carbon material, a dispersant, and a binder. The binder is preferably present at least on the surface of the carbon material layer facing the current collector. This is because the adhesion of the carbon material layer to the current collector is improved. The binder may be present uniformly in the carbon material layer.
[0050] The carbon material layer improves the adhesion between the current collector and the active material layer. The peel strength of the current collector and the active material layer disposed via the carbon material layer is, for example, 0.05 N / cm or more, or may be 0.10 N / cm or more, 0.30 N / cm or more, or may be 0.60 N / cm or more at 80°C. The peel strength of the current collector and the active material layer is, for example, 1 N / cm or less at 80°C. A method for measuring the peel strength will be described in the examples below.
[0051] The carbon material layer has an electronic conductivity (25° C.) of, for example, 20 S / cm or more and 200 S / cm or less. The carbon material layer has a thickness of, for example, 0.5 μm or more, and may be 1 μm or more, or 2 μm or more. On the other hand, the carbon material layer has a thickness of, for example, 15 μm or less, and may be 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.
[0052] The method of forming the carbon material layer is not particularly limited, but may be, for example, a method of coating a slurry containing a carbon material, a dispersing material, a binder, and a dispersing medium on a current collector and drying the slurry. The dispersing medium is preferably, for example, hydrophilic. Carbon materials are usually hydrophobic, and therefore have low affinity with hydrophilic dispersing media. In contrast, it is presumed that the presence of a hydrophilic dispersing material between the carbon material and the dispersing medium will eliminate the aggregation of the carbon material and improve the dispersibility of the carbon material. Examples of hydrophilic dispersing media include water, alcohols, glycols, cellosolves, amino alcohols, amines, ketones, carboxylic acid amides, phosphoric acid amides, sulfoxides, carboxylic acid esters, phosphoric acid esters, ethers, and nitriles. The dispersing medium preferably contains at least water.
[0053] 2. Current collector The current collector in the present disclosure collects current from the active material layer via the carbon material layer. When the electrode in the present disclosure is a positive electrode, the current collector is a positive electrode current collector, and when the electrode in the present disclosure is a negative electrode, the current collector is a negative electrode current collector.
[0054] Examples of the metal elements contained in the positive electrode current collector include Al, Ni, and Fe. The positive electrode current collector may be a single metal element or an alloy containing the metal element as a main component. Examples of the shape of the positive electrode current collector include a foil shape and a mesh shape.
[0055] Examples of the metal elements contained in the negative electrode current collector include Cu, Ni, and Fe. The negative electrode current collector may be a single metal element or an alloy containing the metal element as a main component. Examples of the shape of the negative electrode current collector include a foil shape and a mesh shape.
[0056] The thickness of the current collector is, for example, 0.1 μm or more and 500 μm or less, and may be 1 μm or more and 100 μm or less.
[0057] 3.Active material layer The active material layer in the present disclosure contains at least an active material. When the electrode in the present disclosure is a positive electrode, the active material is a positive electrode active material, and when the electrode in the present disclosure is a negative electrode, the active material is a negative electrode active material.
[0058] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4, Li4Ti5O 12 and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, etc. As the positive electrode active material, sulfur (S) or lithium sulfide (Li2S) may be used.
[0059] In addition, a protective layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material. This is because it can suppress the reaction between the positive electrode active material and the solid electrolyte. An example of the Li-ion conductive oxide is LiNbO3. The thickness of the protective layer is, for example, 0.1 nm or more and 100 nm or less, and may be 1 nm or more and 20 nm or less.
[0060] Examples of the negative electrode active material include metal active materials, carbon active materials, and oxide active materials. Examples of the metal active material include simple metals and metal alloys. Examples of the metal elements contained in the metal active material include Si, Sn, Li, In, and Al. The metal alloy is preferably an alloy containing the above metal elements as a main component. The metal alloy may be a two-component alloy, or a multi-component alloy of three or more components. Examples of the carbon active material include mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the oxide active material include Li4Ti5O 12 Lithium titanates such as those mentioned above are also included.
[0061] The shape of the active material may be, for example, particulate. 50 ) is, for example, 10 nm or more and 50 μm or less, and may be 100 nm or more and 20 μm or less. The proportion of the active material in the active material layer is, for example, 50 wt % or more, and may be 60 wt % or more and 99 wt % or less.
[0062] The active material layer may further contain a solid electrolyte. Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes and oxide solid electrolytes. The sulfide solid electrolyte preferably contains Li, A (A is at least one of P, Si, Ge, Al, and B), and S. The sulfide solid electrolyte preferably has an anion structure with an ortho composition (PS4 3- Structure: SiS4 4- Structure, GeS4 4- Structure: AlS3 3-Structure, BS3 3- It is preferable that the sulfide solid electrolyte has an anion structure having an ortho composition as a main component. The ratio of the anion structure having an ortho composition is, for example, 50 mol % or more, and may be 70 mol % or more, based on the total anion structures in the sulfide solid electrolyte. The sulfide solid electrolyte may contain a lithium halide. Examples of the lithium halide include LiCl, LiBr, and LiI. The solid electrolyte may be glass, crystallized glass (glass ceramics), or a crystalline material. The shape of the solid electrolyte may be, for example, particulate.
[0063] The active material layer may further contain at least one of a conductive material and a binder. Examples of the conductive material include the carbon materials described in "1. Carbon material layer" above. Examples of the binder include fluoride-based binders such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, and fluororubber; and rubber-based binders such as butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber. The binder used in the active material layer is preferably different in type from the binder used in the carbon material layer. For example, the binder used in the active material layer is preferably a fluoride-based binder or a rubber-based binder, and the binder used in the carbon material layer is preferably an acrylic binder or a methacrylic binder.
[0064] The thickness of the active material layer is, for example, 0.1 μm or more and 500 μm or less, and may be 1 μm or more and 100 μm or less.
[0065] 4.Electrode The electrode in the present disclosure has a current collector, an adhesive carbon material layer, and an active material layer in this order in the thickness direction. The electrode in the present disclosure is usually used in an all-solid-state battery. Details of the all-solid-state battery will be described later. The present disclosure can also provide a current collector for use in an all-solid-state battery, the current collector having, on one surface, a carbon material layer that contains a carbon material, a dispersing material, and a binder and has adhesive properties.
[0066] B. All-solid-state battery Fig. 2 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. The all-solid-state battery 100 shown in Fig. 2 includes a positive electrode 10 as a first electrode, a negative electrode 20 as a second electrode, and a solid electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10 corresponds to the electrode described in "A. Electrode" above. That is, the positive electrode 10 includes a positive electrode current collector 1, a carbon material layer 3, and a positive electrode active material layer 2 arranged in a thickness direction D. T The negative electrode 20 has the negative electrode current collector 11 and the negative electrode active material layer 12 in the thickness direction D. T The solid electrolyte layer 30 is disposed between the positive electrode active material layer 2 in the positive electrode 10 and the negative electrode active material layer 12 in the negative electrode 20, in this order.
[0067] According to the present disclosure, at least one of the first electrode and the second electrode is the above-mentioned electrode, and therefore, an all-solid-state battery having good durability at high temperatures is obtained.
[0068] 1. First electrode and second electrode The all-solid-state battery of the present disclosure has a first electrode and a second electrode having a polarity opposite to that of the first electrode. For example, when the first electrode is a positive electrode, the second electrode is a negative electrode. Conversely, when the first electrode is a negative electrode, the second electrode is a positive electrode. When the all-solid-state battery is viewed in plan in the thickness direction, it is preferable that the negative electrode active material layer is disposed so as to encompass the outer edge of the positive electrode active material layer. This is because short circuits caused by dendrites are less likely to occur.
[0069] The first electrode has a first current collector and a first active material layer. If the first electrode corresponds to the electrode described in "A. Electrode" above, the first electrode has a first carbon material layer between the first current collector and the first active material layer. On the other hand, the second electrode has a second current collector and a second active material layer. If the second electrode corresponds to the electrode described in "A. Electrode" above, the second electrode has a second carbon material layer between the second current collector and the second active material layer.
[0070] In the present disclosure, (i) the first electrode may be an electrode described in "A. Electrodes" and the second electrode may not be an electrode described in "A. Electrodes", and (ii) the first electrode and the second electrode may each be an electrode described in "A. Electrodes". In the case of (i), the first electrode may be a positive electrode or a negative electrode.
[0071] 2.Solid electrolyte layer The solid electrolyte layer is a layer disposed between the first electrode and the second electrode. The solid electrolyte layer contains at least a solid electrolyte, and may further contain a binder. The solid electrolyte and the binder are the same as those described in "A. Electrodes" above, and therefore will not be described here. The solid electrolyte layer preferably contains a sulfide solid electrolyte. This is because the sulfide solid electrolyte has high ionic conductivity.
[0072] The proportion of the solid electrolyte in the solid electrolyte layer is, for example, 10% by weight or more and 100% by weight or less, and may be 50% by weight or more and 100% by weight or less. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 500 μm or less, and may be 1 μm or more and 100 μm or less.
[0073] 3.All-solid-state battery The all-solid-state battery in the present disclosure includes a first electrode, a second electrode, and a solid electrolyte layer disposed between the first electrode and the second electrode. Here, when a set of the first electrode, the second electrode, and the solid electrolyte layer is defined as a power generation unit, the all-solid-state battery may have only one power generation unit or may have multiple power generation units. In the latter case, the multiple power generation units may be connected in series or in parallel.
[0074] FIG. 3 is a schematic cross-sectional view illustrating an example of an all-solid-state battery in the present disclosure, specifically, an all-solid-state battery in which a plurality of power generating units are connected in parallel. In FIG. 3, the first electrode is a positive electrode, and the second electrode is a negative electrode. The all-solid-state battery 100 shown in FIG. 3 includes a positive electrode A (positive electrode 10A) and a positive electrode B (positive electrode 10B) as the positive electrode 10. The all-solid-state battery 100 includes a solid electrolyte layer A (solid electrolyte layer 30A) and a solid electrolyte layer B (solid electrolyte layer 30B) as the solid electrolyte layer 30. The negative electrode 20 includes a negative electrode current collector 11, a negative electrode active material layer A (negative electrode active material layer 12a) formed on one surface of the negative electrode current collector 11, and a negative electrode active material layer B (negative electrode active material layer 12b) formed on the other surface of the negative electrode current collector 11. The solid electrolyte layer A (solid electrolyte layer 30A) is disposed between the negative electrode active material layer 12a and the positive electrode active material layer 2a, and the solid electrolyte layer B (solid electrolyte layer 30B) is disposed between the negative electrode active material layer 12b and the positive electrode active material layer 2b.
[0075] The all-solid-state battery 100 shown in FIG. 3 is arranged in a thickness direction D T Since the current collector has a symmetrical structure in the direction of the electrode, it is possible to suppress the occurrence of distortion caused by the difference in the elasticity of the active material layers. For example, when a bipolar electrode is used in which a positive electrode active material layer is arranged on one side of a current collector and a negative electrode active material layer is arranged on the other side, depending on the pressing conditions, distortion may occur in the current collector due to the difference in elasticity between the positive electrode active material layer and the negative electrode active material layer, and cracks may occur in the positive electrode active material layer or the negative electrode active material layer. In contrast, as shown in FIG. 3, by arranging active material layers having the same polarity on both sides of the current collector, there is an advantage in that the occurrence of distortion caused by the difference in elasticity of the active material layers can be suppressed.
[0076] The all-solid-state battery 100 shown in FIG. 3 includes a positive electrode A (positive electrode 10A), a solid electrolyte layer A (solid electrolyte layer 30A), a negative electrode 20, a solid electrolyte layer B (solid electrolyte layer 30B), and a positive electrode B (positive electrode 10B) arranged in a thickness direction D T 3, both positive electrode A and positive electrode B correspond to the electrodes described in "A. Electrode" above. That is, positive electrode A (positive electrode 10A) includes a positive electrode current collector 1a, a first carbon material layer 3a, and a positive electrode active material layer 2a arranged in the thickness direction D. T Similarly, the positive electrode B (positive electrode 10B) has a positive electrode current collector 1b, a second carbon material layer 3b, and a positive electrode active material layer 2b arranged in the thickness direction D. T In this order:
[0077] In FIG. 3, both the positive electrode A and the positive electrode B correspond to the electrodes described in the above "A. Electrode", but only one of the positive electrode A and the positive electrode B may correspond to the electrodes described in the above "A. Electrode". Also, in FIG. 3, the first electrode is a positive electrode and the second electrode is a negative electrode, but this relationship may be reversed. That is, the positive electrode in FIG. 3 may be a negative electrode, and the negative electrode in FIG. 3 may be a positive electrode. In that case, both the negative electrode A and the negative electrode B may correspond to the electrodes described in the above "A. Electrode", or only one of the negative electrode A and the negative electrode B may correspond to the electrodes described in the above "A. Electrode".
[0078] The all-solid-state battery in the present disclosure may include an exterior body that houses the power generating element (first electrode, second electrode, and solid electrolyte layer). Examples of the exterior body include a laminate-type exterior body and a case-type exterior body. In addition, the all-solid-state battery in the present disclosure may be applied with a confining pressure by a confining jig, or may not be applied with a confining pressure by a confining jig. Since the carbon material layer in the present disclosure has good adhesion at high temperatures, even if a confining pressure is not applied by a confining jig, the all-solid-state battery has low resistance. On the other hand, when a confining pressure is applied by a confining jig, the confining pressure may be, for example, 1 MPa or more and 50 MPa or less, or 5 MPa or more and 20 MPa or less.
[0079] The type of the all-solid-state battery in the present disclosure is not particularly limited, but is typically a lithium-ion secondary battery. Furthermore, the use of the all-solid-state battery in the present disclosure is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the all-solid-state battery in a driving power source for a hybrid electric vehicle, a plug-in hybrid electric vehicle, or an electric vehicle. In addition, the all-solid-state battery in the present disclosure may be used as a power source for a moving body other than a vehicle (for example, a train, a ship, or an aircraft), or as a power source for an electrical product such as an information processing device.
[0080] C. Manufacturing method of all-solid-state batteries FIG. 4 is a schematic cross-sectional view illustrating a method for manufacturing an all-solid-state battery according to the present disclosure. FIG. 4 illustrates a case where the first electrode is a positive electrode and the second electrode is a negative electrode. In the method for manufacturing an all-solid-state battery shown in FIG. 4, first, a negative electrode collector 11 is prepared (FIG. 4(a)). Next, a negative electrode active material layer A (negative electrode active material layer 12a) is formed on one surface of the negative electrode collector 11, and a negative electrode active material layer B (negative electrode active material layer 12b) is formed on the other surface of the negative electrode collector 11. This results in a negative electrode 20 (FIG. 4(b)). As a method for forming the negative electrode active material layer, for example, a method in which a slurry for forming the negative electrode active material layer is applied onto the negative electrode collector 11 and then dried can be mentioned. If necessary, the negative electrode 20 may be pressed.
[0081] Next, a solid electrolyte layer A (solid electrolyte layer 30A) is formed on the negative electrode active material layer A (negative electrode active material layer 12a), and a solid electrolyte layer B (solid electrolyte layer 30B) is formed on the negative electrode active material layer B (negative electrode active material layer 12b), to obtain a laminate X (FIG. 4(c)). The solid electrolyte layer can be formed, for example, by a transfer method. For example, the transfer method can be a method in which a transfer member having a substrate and a solid electrolyte layer is prepared, the solid electrolyte layer on the transfer member and the negative electrode active material layer are placed so as to face each other, pressed, and then the substrate is peeled off from the solid electrolyte layer.
[0082] Next, a first active material layer A (first active material layer 2a) is formed on the solid electrolyte layer A (solid electrolyte layer 30A) in the laminate X, and a first active material layer B (first active material layer 2b) is formed on the solid electrolyte layer B (solid electrolyte layer 30B) in the laminate X to obtain a laminate Y (FIG. 4(d)). The method for forming the first active material layer includes, for example, a transfer method. As the transfer method, for example, a method is included in which a transfer member having a substrate and a first active material layer is prepared, and the first active material layer and the solid electrolyte layer in the transfer member are arranged to face each other and pressed, and then the substrate is peeled off from the first active material layer. Thereafter, although not particularly shown, a press process is performed to densify the laminate Y. As a result, the first active material layer A (first active material layer 2a), the solid electrolyte layer A (solid electrolyte layer 30A), the negative electrode active material layer A (negative electrode active material layer 12a), the second current collector 11, the negative electrode active material layer B (negative electrode active material layer 12b), the solid electrolyte layer B (solid electrolyte layer 30B), and the first active material layer B (first active material layer 2b) are arranged in a thickness direction D T A precursor laminate having the above-mentioned steps is obtained.
[0083] Next, the first current collector A (first current collector 1a) is placed on the first active material layer A (first active material layer 2a) in the precursor laminate, with a first carbon material layer 3a containing a carbon material, a dispersant, and a binder interposed therebetween (FIG. 4(e)). Similarly, the first current collector B (first current collector 1b) is placed on the first active material layer B (first active material layer 2b) in the precursor laminate, with a second carbon material layer 3b containing a carbon material, a dispersant, and a binder interposed therebetween (FIG. 4(e)). In this way, an all-solid-state battery 100 is obtained.
[0084] According to the present disclosure, by disposing the first current collector A on the first active material layer A via the first carbon material layer, an all-solid-state battery having good durability at high temperatures can be obtained. For example, in the above-mentioned FIG. 4, in order to densify the laminate Y, pressing is performed at high pressure (densification pressing). At that time, if the laminate Y has the first current collector A, the first active material layer A may not be sufficiently densified, or the first current collector A may be damaged. Therefore, it is preferable that the laminate Y is densified and pressed without the first current collector A. In addition, it is preferable to dispose the first current collector A on the first active material layer A after the densification pressing. In the present disclosure, by disposing the first current collector A on the first active material layer A via the first carbon material layer, an all-solid-state battery having good durability at high temperatures can be obtained.
[0085] 1. Preparation process The preparation step in the present disclosure is a step of preparing a precursor laminate having a first active material layer A, a solid electrolyte layer A, a second active material layer A, a second current collector, a second active material layer B, a solid electrolyte layer B, and a first active material layer B, in this order in the thickness direction.
[0086] The method for preparing the precursor laminate is not particularly limited, but may be, for example, the method shown in Fig. 4(a) to (d) above. Each layer constituting the precursor laminate is the same as that described in "B. All-solid-state battery" above.
[0087] 2.First placement process The first arrangement step in the present disclosure is a step of arranging a first current collector A on the first active material layer A of the precursor laminate via a first carbon material layer containing a carbon material, a dispersion material, and a binder.
[0088] The first carbon material layer may be formed in advance on the first current collector A, or may be formed in advance on the first active material layer A. Alternatively, a transfer member having a substrate and the first carbon material layer may be used to transfer the first carbon material layer to the first active material layer A or the first current collector A immediately before the first active material layer A and the first current collector A are opposed to each other. The first carbon material layer and the first current collector A are the same as those described above in "B. All-solid-state battery."
[0089] 3.Second placement process The method for producing an all-solid-state battery according to the present disclosure usually includes a second disposing step of disposing a first current collector B on the first active material layer B in the precursor laminate. The first current collector B may be disposed directly on the first active material layer B, or the first current collector B may be disposed on the first active material layer B via another layer. An example of the other layer is a second carbon material layer containing a carbon material, a dispersant, and a binder.
[0090] The second carbon material layer may be formed in advance on the first current collector B, or may be formed in advance on the first active material layer B. Alternatively, a transfer member having a substrate and the second carbon material layer may be used to transfer the second carbon material layer to the first active material layer B or the first current collector B immediately before the first active material layer B and the first current collector B are placed opposite each other. The second carbon material layer and the first current collector B are the same as those described above in "B. All-solid-state battery".
[0091] 4.All-solid-state battery The all-solid-state battery obtained by each of the above-mentioned steps is similar to that described in "B. All-solid-state battery" above, so the description here is omitted.
[0092] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0093] [Example 1] (Preparation of Positive Electrode Active Material Having a Coating Layer) Cathode active material (Li 1.15 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 The particles (main phase of which is O2) were coated with lithium niobate in an air atmosphere using a rolling fluidized coating device (manufactured by Powrex Corporation), and sintered in an air atmosphere. This resulted in a positive electrode active material having a coating layer of lithium niobate.
[0094] (Preparation of Positive Electrode Active Material Layer) A positive electrode active material, a sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a binder (PVDF), a conductive material (VGCF, manufactured by Showa Denko K.K.) and a dispersion medium were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT K.K.). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and further stirred for 30 seconds with an ultrasonic dispersion device. Next, the mixture was shaken for 3 minutes with a shaker to obtain a slurry. The obtained slurry was applied to a substrate (aluminum foil) by a blade method using an applicator. Next, the mixture was naturally dried, and further dried for 30 minutes on a hot plate at 100 ° C. This formed a positive electrode active material layer on the aluminum foil as a substrate. The amount of the slurry applied was adjusted so that the thickness of the positive electrode active material layer was 15 μm in a state after densification described later.
[0095] (Preparation of negative electrode) A negative electrode active material (LTO particles), a sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a binder (PVDF), a conductive material (VGCF, Showa Denko K.K.) and a dispersion medium were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersion device (UH-50, SMT Corporation). Next, the container was shaken for 3 minutes with a shaker (TTM-1, Shibata Scientific Co., Ltd.), and further stirred for 30 seconds with an ultrasonic dispersion device. Next, the mixture was shaken for 3 minutes with a shaker to obtain a slurry. The obtained slurry was applied to a negative electrode current collector (copper foil) by a blade method using an applicator. Next, the mixture was naturally dried, and further dried for 30 minutes on a hot plate at 100 ° C. This formed a negative electrode active material layer on one surface of the negative electrode current collector (copper foil). By the same operation, a negative electrode active material layer was also formed on the other surface of the negative electrode current collector (copper foil). In this manner, a negative electrode was obtained in which a negative electrode active material layer was disposed on each side of a negative electrode current collector (copper foil).
[0096] (Preparation of solid electrolyte layer) A sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a binder (BR), and a dispersion medium (heptane) were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Corporation). Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and further stirred for 30 seconds with an ultrasonic dispersion device. Next, the mixture was shaken for 3 minutes with a shaker to obtain a slurry. The obtained slurry was applied to a substrate (aluminum foil) by a blade method using an applicator. Next, the mixture was naturally dried, and further dried on a hot plate at 100°C for 30 minutes. As a result, a solid electrolyte layer was formed on the aluminum foil substrate.
[0097] (Preparation of a positive electrode current collector having a carbon material layer) Conductive material (acetylene black, AB, oil absorption: 175 cm 3A conductive material (100g / 100g), a binder (acrylic binder, Tg: -30°C), and a dispersing agent (polyvinyl alcohol) were weighed out so that the weight ratio of conductive material:binder:dispersing agent was 25:50:25. A dispersing medium (water) was then added to these to obtain a slurry for the carbon material layer. The obtained slurry was applied onto a positive electrode current collector (aluminum foil) by a blade method using an applicator. The mixture was then dried at 120°C. As a result, a positive electrode current collector having a carbon material layer was obtained.
[0098] (Production of all-solid-state batteries) A solid electrolyte layer was placed on each side of the negative electrode, and pressed at a linear pressure of 1.6 t / cm. Next, the base material (aluminum foil) was peeled off from the solid electrolyte layer to obtain a laminate X having a solid electrolyte layer A, a negative electrode, and a solid electrolyte layer B. Next, a positive electrode active material layer was placed on the surface of each of the solid electrolyte layer A and the solid electrolyte layer B, and pressed at a linear pressure of 1.6 t / cm. Next, the base material (aluminum foil) was peeled off from the positive electrode active material layer to obtain a laminate Y. Next, the laminate Y was pressed at a linear pressure of 5 t / cm to be densified. This resulted in a precursor laminate having a positive electrode active material layer A, a solid electrolyte layer A, a negative electrode, a solid electrolyte layer B, and a positive electrode active material layer B. Next, the positive electrode was laser trimmed to 70.0 mm x 70.0 mm, and the negative electrode was cut to 72.0 mm x 72.0 mm. Next, a positive electrode current collector having a carbon material layer was placed on each of the positive electrode active material layers A and B, and 10 such laminates were stacked and pressed at 140°C, 5 MPa, and 1 hour to obtain a power generating element. A terminal was attached to the obtained power generating element by welding, and the element was enclosed in a laminate cell to obtain an all-solid-state battery.
[0099] [Examples 2 to 7] An all-solid-state battery was obtained in the same manner as in Example 1, except that the type of acrylic binder and the composition of the slurry for the carbon material layer were changed to those shown in Table 1.
[0100] [Comparative Examples 1 and 2] An all-solid-state battery was obtained in the same manner as in Example 1, except that the type of acrylic binder and the composition of the slurry for the carbon material layer were changed to those shown in Table 2.
[0101] [evaluation] (Resistance measurement) The resistance of the all-solid-state batteries obtained in Examples 1 to 7 and Comparative Examples 1 and 2 was measured. Specifically, CCCV charging was performed at a current value of 0.3 C to 2.85 V, and then CCCV discharging was performed at a current value of 0.3 C to 2.5 V. Thereafter, CC discharging was performed under conditions of 15 C, 2 seconds, and 25° C., and the resistance was calculated from the voltage change at that time. The results are shown in Tables 1 and 2.
[0102] (Peel strength measurement) The peel strength of the positive electrode current collector and the positive electrode active material layer was measured using the all-solid-state batteries obtained in Examples 1 to 7 and Comparative Examples 1 and 2. As shown in Fig. 5, the all-solid-state battery was cut to a width of 20 mm, the back side was fixed to a base, and a peel test was performed in accordance with JIS Z 0237 in which the tab 1t of the positive electrode current collector 1 was lifted in a 90° direction to peel it off, and the peel strength at 80°C was measured. The results are shown in Tables 1 and 2 and Fig. 6.
[0103] (High temperature storage test) A high-temperature storage test was carried out on the all-solid-state batteries obtained in Examples 1 to 7 and Comparative Examples 1 and 2. Specifically, the all-solid-state batteries were stored in a temperature environment of 80° C. for three months. The resistance at 80° C. was measured before and after storage. The results are shown in Tables 1 and 2 and FIG. 7.
[0104] [Table 1]
[0105] [Table 2]
[0106] As shown in Tables 1, 2 and FIG. 6, it was confirmed that Examples 1 to 7 using a dispersion material had a higher peel strength at 80°C than Comparative Examples 1 and 2 not using a dispersion material. In addition, when the weight ratio of the binder to the carbon material was 2.0 or more, the increase in peel strength became significant. In particular, when the weight ratio of the binder to the carbon material was 2.8 or more, a very high peel strength was obtained. In this way, it was confirmed that by adding a dispersion material to the carbon material layer, an electrode having good adhesion between the current collector and the active material layer at high temperatures can be obtained.
[0107] Moreover, as shown in FIG. 7, before the high-temperature storage test, Examples 1 to 7 and Comparative Examples 1 and 2 all had similar resistances. On the other hand, after the high-temperature storage test, Examples 1 to 7 were able to suppress the increase in resistance more than Comparative Examples 1 and 2. In Examples 1 to 7, it was expected that the resistance would increase as the weight ratio of the binder to the carbon material increased, but surprisingly, no increase in resistance was confirmed. This is presumably because the dispersibility of the carbon material in the carbon material layer was improved, so that a good ion conduction path was maintained even when the weight ratio of the binder increased. [Explanation of symbols]
[0108] 1...Positive electrode current collector 2...Cathode active material layer 3…Carbon material layer 10...Positive electrode 11...Negative electrode current collector 12...Negative electrode active material layer 20...Negative electrode 30…Solid electrolyte layer 100…All-solid-state battery
Claims
1. An electrode for use in an all-solid-state battery, The electrode has a current collector, an adhesive carbon material layer, and an active material layer in this order in a thickness direction, The carbon material layer contains a carbon material, a dispersion material, and a binder, the carbon material layer contains the binder as a main component, The electrode, wherein the dispersion material includes at least one of a vinyl resin and a cellulose derivative.
2. The electrode according to claim 1 , wherein the proportion of the dispersed material in the carbon material layer is 1% by weight or more.
3. 3. The electrode according to claim 1, wherein the proportion of the dispersed material in the carbon material layer is 35% by weight or less.
4. 4. The electrode according to claim 1, wherein in the carbon material layer, a weight ratio of the dispersed material to the carbon material is 0.05 or more and 1.2 or less.
5. 5. The electrode according to claim 1, wherein the proportion of the binder in the carbon material layer is 50% by weight or more.
6. 6. The electrode according to claim 1, wherein in the carbon material layer, a weight ratio of the binder to the carbon material is 2.0 or more.
7. 7. The electrode according to claim 1, wherein in the carbon material layer, a weight ratio of the binder to the carbon material is 2.8 or more.
8. 8. The electrode of claim 1, wherein the dispersion comprises polyvinyl alcohol.
9. 9. The electrode of claim 1, wherein the binder comprises at least one of an acrylic binder and a methacrylic binder.
10. The oil absorption of the carbon material is 175 cm 3 10. The electrode according to claim 1, wherein the surface area of the electrode is 100 g or more.
11. 11. The electrode of claim 1, wherein the carbon material comprises carbon black.
12. The electrode according to claim 1 , wherein the binder is present at least on a surface of the carbon material layer that faces the current collector.
13. 13. The electrode according to claim 1, wherein the peel strength between the current collector and the active material layer is 0.10 N / cm or more at 80°C.
14. An all-solid-state battery comprising a first electrode, a second electrode, and a solid electrolyte layer disposed between the first electrode and the second electrode, An all-solid-state battery, wherein at least one of the first electrode and the second electrode is the electrode according to any one of claims 1 to 13.
15. The all-solid-state battery includes a first electrode A and a first electrode B as the first electrode, and includes a solid electrolyte layer A and a solid electrolyte layer B as the solid electrolyte layer, the second electrode has a second current collector, a second active material layer A formed on one surface of the second current collector, and a second active material layer B formed on the other surface of the second current collector, The all-solid-state battery has the first electrode A, the solid electrolyte layer A, the second electrode, the solid electrolyte layer B, and the first electrode B, in this order in a thickness direction, The all-solid-state battery according to claim 14 , wherein at least one of the first electrode A and the first electrode B is the electrode.
16. a preparation step of preparing a precursor laminate having a first active material layer A, a solid electrolyte layer A, a second active material layer A, a second current collector, a second active material layer B, a solid electrolyte layer B, and a first active material layer B in this order in a thickness direction; a first disposing step of disposing a first current collector A on the first active material layer A of the precursor laminate via a first carbon material layer containing a carbon material, a dispersing material, and a binder; having the first carbon material layer contains the binder as a main component, The method for producing an all-solid-state battery, wherein the dispersion material contains at least one of a vinyl resin and a cellulose derivative.
17. 17. The method for producing an all-solid-state battery according to claim 16, further comprising a second disposing step of disposing a first current collector B on the first active material layer B of the precursor laminate via a second carbon material layer containing a carbon material, a dispersion material, and a binder.
Citation Information
Patent Citations
Method for manufacturing all-solid secondary battery
JP2012243476A
Filtration filter of slurry for active material layer formation
JP2014102967A
Nonaqueous electrolyte secondary battery
JP2015103332A
All-solid battery
JP2017204377A
Conductive particle, conductive material and connection structure
JP2019021635A